Pengembangan Media Pembelajaran Ular Tangga Bermuatan Aqidah: Studi Pada Materi Iman Kepada Hari Akhir di MTs Darul Amin Palangka Raya - Rowina, Sinta; Jennah, Rodhatul; Gofur, Abdul (Jayapangus Press, 2025)
Based on the results of the researcher's observations, there are problems in the use of conventional and passive learning media. In solving these problems, the researcher developed a snake and ladder game media on the material of faith in the hereafter which is the 5th pillar of faith. Limited distribution was only carried out at MTs Darul Amin Palangkaraya school. Another goal is to find out whether the snake and ladder game media is suitable for use as a learning medium. This study uses a research and development method with the 4D Thiagaraja model. This stage consists of define, design, develop, and disseminate. Based on the results of the study, the results of the validation of material experts obtained an average percentage of 87% with the criteria